2005
DOI: 10.1179/174367605x46830
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer at oxygen/zirconia interface at elevated temperatures: Part 9: Room temperature

Abstract: The present paper reports the reactivity between the surface of zirconia and oxygen at room temperature. The experimental studies, performed with polycrystalline yttria-stabilised zirconia (YSZ), include in situ monitoring of charge transfer at the oxygen/zirconia interface using work function measurements and determination of mass transport at the oxygen/zirconia interface using the incorporation of oxygen isotope 18 O and its analysis using secondary ion mass spectrometry. Oxidation of YSZ at room temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…The studies of Nowotny et al have shown that these two assumptions are in question. First, it has been documented that oxidation of YSZ does not require the presence of an electronic conductor .…”
Section: Postulation Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies of Nowotny et al have shown that these two assumptions are in question. First, it has been documented that oxidation of YSZ does not require the presence of an electronic conductor .…”
Section: Postulation Of the Problemmentioning
confidence: 99%
“…It has also been commonly assumed that the presence of an electronic conductor attached to the surface of YSZ, such as platinum, is essential for oxygen incorporation from the gas phase into the YSZ lattice. However, the studies of surface semiconducting properties of YSZ indicate that (i) oxygen may react with the surface of YSZ without the presence of an electronic conductor and (ii) the charge transport within the YSZ-based electrochemical devices is determined by the electric field induced by gradients in chemical composition in the outermost surface layer rather than bulk diffusion. In other words, it has been documented that, while YSZ is a poor electronic conductor, the local concentration of electronic charge carriers at the surface is high enough to allow the charge transfer during oxidation of YSZ in the absence of an electronic conductor.…”
Section: Introductionmentioning
confidence: 99%
“…54,69 In addition, the present study shows that oxidation of electrodeless YSZ results in oxygen chemisorption and oxygen incorporation. [6][7][8][9][10] The preceding evidence leads to a general model as depicted in Fig. 5 (this is an analogue of Fig.…”
Section: Biphase Oxygen/zirconia Boundarymentioning
confidence: 79%
“…The present study has therefore determined the effect of temperature on the kinetics of the reactivity of YSZ with oxygen in terms of oxygen chemisorption and oxygen incorporation. 6,8,9 It has been shown that oxygen incorporates into the lattice in the entire temperature range studied (300-1173 K). The results obtained allow the effect of temperature on oxygen chemisorption to be established in terms of the stability of specific oxygen species and their surface coverage, and the determination of oxygen chemisorption isobars.…”
Section: Surface Reactivity Of Ysz With Oxygenmentioning
confidence: 97%
“…5,6 It has also established the effect of surface properties and temperature on reactivity between YSZ and oxygen in terms of the electrical effects accompanying both processes, namely oxygen chemisorption and oxygen incorporation. [7][8][9][10][11] Effect of temperature on reactivity It is well known that the performance of YSZ depends critically on temperature. The present study has therefore determined the effect of temperature on the kinetics of the reactivity of YSZ with oxygen in terms of oxygen chemisorption and oxygen incorporation.…”
Section: Surface Reactivity Of Ysz With Oxygenmentioning
confidence: 99%